Cytotoxicity of TiO2 nanoparticles to mussel hemocytes and gill cells in vitro: Influence of synthesis method, crystalline structure, size and additive. Issue 5 (August 2015) - Katsumiti, Alberto; Berhanu, Deborah; Howard, Kieren T.; Arostegui, Inmaculada; Oron, Miriam; Reip, Paul; Valsami-Jones, Eugenia; Cajaraville, Miren P.
Abstract Increasing the production and applications of TiO2 nanoparticles (NPs) has led to grow concerns about the consequences for the environment. In this study, we investigated the effects of a set of TiO2 NPs on the viability of mussel hemocytes and gill cells using neutral red and thiazolyl tetrazolium bromide assays. For this, we compared the cytotoxicity of TiO2 NPs (0.1–100 mg Ti/L) produced by different techniques: rutile NPs (60 nm) produced by milling and containing disodium laureth sulfosuccinate (DSLS), rutile NPs (10, 40 and 60 nm) produced by wet chemistry and anatase/rutile NPs (∼100 nm) produced by plasma synthesis. The commercially available P25 anatase/rutile NPs (10–20 nm) were also tested. Exposures were performed in parallel with their respective bulk forms and the cytotoxicity of the additive DSLS was also tested. Z potential values in distilled water indicated different stabilities depending on the NP type and all NPs tested formed agglomerates/aggregates in cell culture media. In general, TiO2 NPs showed a relatively low and dose-dependent toxicity for both cell models with the two assays tested. NPs produced by milling showed the highest effects, probably due to the toxicity of DSLS. Size-dependent toxicity was found for NPs produced by wet chemistry (10 nm > 40 nm and 60 nm). All TiO2 NPs tested were more toxic than bulk forms excepting for plasma produced ones, which were the least toxic TiO2 tested. The mixture bulk anatase/rutile TiO2 was more toxic than bulk rutile TiO2. In conclusion, the toxicity of TiO2 NPs varied with the mode of synthesis, crystalline structure and size of NPs and can also be influenced by the presence of additives in the suspensions.